In vitro fertilization is associated with an increased risk of borderline ovarian tumours - Stewart, Louise; Holman, C.; Finn, Judith; Preen, D.; Hart, R. (Elsevier Inc, 2013)
Objectives: To compare the risk of borderline ovarian tumours in women having in vitro fertilization (IVF) with women diagnosed with infertility but not having IVF. Methods: This was a whole-population cohort study of women aged 20–44 years seeking hospital infertility treatment or investigation in Western Australia in 1982–2002. Using Cox regression, we examined the effects of IVF treatment and potential confounders on the rate of borderline ovarian tumours. Potential confounders included parity, age, calendar year, socio-economic status, infertility diagnoses including pelvic inflammatory disorders and endometriosis and surgical procedures including hysterectomy and tubal ligation. Results: Women undergoing IVF had an increased rate of borderline ovarian tumours with a hazard ratio (HR) of 2.46 (95% confidence interval [CI] 1.20–5.04). Unlike invasive epithelial ovarian cancer, neither birth (HR 0.89; 95% CI 0.43–1.88) nor hysterectomy (1.02; 0.24–4.37) nor sterilization (1.48; 0.63–3.48) appeared protective and the rate was not increased in women with a diagnosis of endometriosis (HR 0.31; 95% CI 0.04–2.29). Conclusions: Women undergoing IVF treatment are at increased risk of being diagnosed with borderline ovarian tumours. Risk factors for borderline ovarian tumours appear different from those for invasive ovarian cancer.